Development of Communication Media, Information, and Education on Safe, Comfortable, and Healthy Bicycle Movements - Prayogi Dwina Angga; Deddy Whinata (Journal Of Sport Education (JOPE), 2024)
This research and development aim to produce communication, information and education media products for safe, comfortable and healthy bicycle movements. The research and development approach for educational media posters and leaflets adapts the stages of research and development by Borg and Gall which outlines 4 stages, namely: (1) preliminary study; (2) planning and development; (3) validation, evaluation and revision; (4) implementation. This research and development was carried out in Malang city and Solo city using the target target bicycle community. Data analysis techniques used in research and development use qualitative and quantitative approaches. Qualitative data is obtained from the results of open questions. Quantitative data is obtained through the results of filling out questionnaires conducted in expert validation tests, small group trials and large group trials. The results of the validation test conducted by material experts and media experts obtained a percentage of 86% and 83.13% respectively. The results of the small group trial obtained a percentage value of 89.19%, while in the large group trial obtained a percentage value of 89.30%. All the results of testing the product both at the validity and practicality test stages have very good criteria. It is hoped that this media will become an instrument that can increase knowledge and change the behavior of communities or individuals by implementing cycling behavior properly and correctly.